Pancasila as the Core Value for Character Building in Islamic Higher Education Institutions - ZA, Tabrani; Walidin, Warul; Idris, Saifullah; Huda, Miftachul (SCAD Independent, 2024)
Higher education, as the continuation and culmination of the formal education process, has a role and responsibility to optimize character building based on the nation’s philosophy, namely Pancasila. Indonesia today is far from Pancasila’s hopes. This article explored the landscape of internalizing the nation’s philosophical values through exposure to concepts, practices, and challenges at UIN Ar-Raniry. This research used qualitative methods with a naturalistic approach carried out at Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia. The sample in this study was taken using a non-probability sampling technique. Meanwhile, data collection was carried out using triangulation techniques. The data were analyzed using inductive analysis techniques with an interactive qualitative approach, comprising data reduction, data display, and drawing conclusions. The research results showed that the process of internalizing the nation’s philosophical values at UIN Ar-Raniry was integrated with the tri-dharma of higher education. The values that were built included fundamental, instrumental, and practical values, which were crystallized into five basic character values: religion, nationalism, independence, mutual cooperation, and integrity. Additionally, the university strengthened character through religious moderation activities, Ma’had al-Jami’ah, and other activities supporting student character building, as evidenced by certificates that were integrated with the academic system through a Diploma Accompanying Certificate, also known as SKPI.